2022
DOI: 10.3390/biology12010047
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Compounds from Pathogenic Bacterium Pseudoalteromonas piscicida X-8 Cause Bleaching Disease, Triggering Active Defense Responses in Commercially Farmed Saccharina japonica

Abstract: Pathogenic bacteria can trigger active defense responses in higher plants, leading to hypersensitive programmed cell death (PCD) to against those bacteria. However, related research on seaweeds is very limited. Pseudoalteromonas piscicida X-8 (PpX-8) has been identified as the pathogen that causes bleaching disease in commercially farmed Saccharina japonica. In this study, using an inoculation assay and microscopic observations, we found that the proportion of bleaching tissue pieces inoculated with PpX-8 extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…68,69 Laboratory experiments have demonstrated that extracellular compounds from the Pseudoalteromonas strain induce similar defense responses leading to programmed cell death, and disease development in S. japonica. 70 On the dominance of Enterobacterales in diseased kelp, Enterobacterales, particularly the MAGs of Pseudoalteromonas, were found to harbor a repertoire of genotypic determinants encoding pathogen-associated factors such as chemotaxis, motility, secretion systems, and pathogenic biofilm formation (Supporting Information). Although these traits are not directly related to bacterial pathogenesis, they are known to aid pathogenic bacteria in manipulating host cell signaling, evading the host immune system, and strengthening their adherence to host cells and tissues, which is a critical step in establishing an infection.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…68,69 Laboratory experiments have demonstrated that extracellular compounds from the Pseudoalteromonas strain induce similar defense responses leading to programmed cell death, and disease development in S. japonica. 70 On the dominance of Enterobacterales in diseased kelp, Enterobacterales, particularly the MAGs of Pseudoalteromonas, were found to harbor a repertoire of genotypic determinants encoding pathogen-associated factors such as chemotaxis, motility, secretion systems, and pathogenic biofilm formation (Supporting Information). Although these traits are not directly related to bacterial pathogenesis, they are known to aid pathogenic bacteria in manipulating host cell signaling, evading the host immune system, and strengthening their adherence to host cells and tissues, which is a critical step in establishing an infection.…”
Section: ■ Discussionmentioning
confidence: 99%
“…However, the outcome and induction of the disease depend on the strength of the interactions between the host, pathogen, and environmental stressors. , Laboratory experiments have demonstrated that extracellular compounds from the Pseudoalteromonas strain induce similar defense responses leading to programmed cell death, and disease development in S. japonica …”
Section: Discussionmentioning
confidence: 99%
“…Pseudoalteromonas piscicida , another highly abundant bacteria found in the sampled mesoplastics from this study, was previously identified as a pathogen that causes bleaching disease in commercially farmed brown algae Saccharina japonica [ 103 ]. In addition, Planctomycetes, traditionally recognized as an environmental bacteria, have recently been linked to human pathology as opportunistic pathogens, arousing a great interest for clinical microbiologists [ 104 ].…”
Section: Discussionmentioning
confidence: 99%